Evidence for extreme floods in arid subtropical northwest Australia during the Little Ice Age chronozone (CE 1400-1850) - Rouillard, A.; Skrzypek, G.; Turney, C.; Dogramaci, S.; Hua, Q.; Zawadzki, A.; Reeves, J.; Greenwood, Paul; O'Donnell, A.; Grierson, P. (Pergamon, 2016)
Here we report a ~2000-year sediment sequence from the Fortescue Marsh (Martuyitha) in the eastern Pilbara region, which we have used to investigate changing hydroclimatic conditions in the arid subtropics of northwest Australia. The Pilbara is located at the intersection of the tropical Indian and Pacific Oceans and its modern rainfall regime is strongly influenced by tropical cyclones, the Intertropical Convergence Zone (ITCZ) and the Indo-Pacific Warm Pool. We identified four distinct periods within the record. The most recent period (P1: CE ~1990-present) reveals hydroclimatic conditions over recent decades that are the most persistently wet of potentially the last ~2000 years. During the previous centuries (P2: ~CE 1600-1990), the Fortescue Marsh was overall drier but likely punctuated by a number of extreme floods, which are defined here as extraordinary, strongly episodic floods in drylands generated by rainfall events of high volume and intensity. The occurrence of extreme floods during this period, which encompasses the Little Ice Age (LIA; CE 1400-1850), is coherent with other southern tropical datasets along the ITCZ over the last 2000 years, suggesting synchronous hydroclimatic changes across the region. This extreme flood period was preceded by several hundred years (P3: ~CE 700-1600) of less vigorous but more regular flows. The earliest period of the sediment record (P4: ~CE 100-700) was the most arid, with sedimentary and preservation processes driven by prolonged drought. Our results highlight the importance of developing paleoclimate records from the tropical and sub-tropical arid zone, providing a long-term baseline of hydrological conditions in areas with limited historical observations.